2020
DOI: 10.1038/s41598-020-69923-x
|View full text |Cite
|
Sign up to set email alerts
|

Discrete finger sequences are widely represented in human striatum

Abstract: Research in primates and rodents ascribes the striatum a critical role in integrating elementary movements into unitary action sequences through reinforcement-based learning. Yet it remains to be shown whether the human striatum represents action sequence-specific information. Young right-handed volunteers underwent functional magnetic resonance imaging while they performed four discrete finger sequences with their right hand, consisting of five button presses. Specific finger sequences could be discriminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(91 reference statements)
2
5
2
Order By: Relevance
“…Although the multivoxel patterns in the bilateral associative putamen showed similar task by stimulation modulation as the sensorimotor part, these effects did not reach significance (see Supplemental Table S3). This stands in contrast with previous reports of motor sequence learning-related modulations of associative striatum multivariate patterns 14,18 and with our earlier work suggesting that inhibitory stimulation resulted in greater maintenance of associative striatum recruitment during MSL 12 . It is worth noting, however, that most of the effects discussed above were observed in the caudate nucleus rather than in the associative portion of the putamen investigated in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the multivoxel patterns in the bilateral associative putamen showed similar task by stimulation modulation as the sensorimotor part, these effects did not reach significance (see Supplemental Table S3). This stands in contrast with previous reports of motor sequence learning-related modulations of associative striatum multivariate patterns 14,18 and with our earlier work suggesting that inhibitory stimulation resulted in greater maintenance of associative striatum recruitment during MSL 12 . It is worth noting, however, that most of the effects discussed above were observed in the caudate nucleus rather than in the associative portion of the putamen investigated in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, the effect of task condition - observed in the current study under the effect of inhibitory stimulation - is in line with previous research reporting sequence-learning-related modulation of striatal multivariate patterns 14,18,24 . Specifically, these recent studies have shown that (sensorimotor) striatal patterns can not only discriminate different motor sequences 18 but also different motor sequence learning stages (e.g., new vs. learned sequences 14,24 ; early versus late stages of initial learning 18 ), although some of these effects might only be observed during full speed as compared to paced motor performance 14 . Our results confirm these previous findings and suggest that learning-related modulation of sensorimotor putamen patterns are preferentially observed under inhibitory stimulation condition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this view, neuroimaging, lesion and animal electrophysiological data all converge to pinpoint a role for the putamen in the integration of movement units and stimulus associations to produce behaviour with a predicted outcome 5155 . Indeed, the neurophysiological properties of the putamen are supported by a subpopulation of neurons that respond to sensory stimuli 56 , unifying actions sets for movement sequences 57, 58 or integrating elementary movement units such as individual finger moves 59 . Moreover, its activity is not solely dedicated to movement parameters, but also in the absence of motor plans 60 , increasing response magnitude to the reinforced choice 61 and for predicted well-learned and contextually-driven actions 6267 .…”
Section: Discussionmentioning
confidence: 99%
“…Because flexible motor sequences can be equated to serial action selection or decision making 26,37 , it follows from BG's acknowledged role in these processes 20,32,38,39 that they should be central to flexible motor sequencing. While recordings showing sequence-specific neural activity in the primate and human BG are consistent with this view 40,41 , more recent studies have called this into question. For example, inactivating a main output nucleus of the BG (GPi) in monkeys did not affect their ability to generate visually guided reaching sequences beyond reducing the speed and/or amplitude of the constituent movements 42 .…”
Section: Introductionmentioning
confidence: 92%